TINGKAT PENGETAHUAN PENGGUNAAN ANTIBIOTIK DENGAN RESEP DOKTER DI APOTEK DEVAN KABUPATEN GOWA - Muhammad Tahir, Muhammad Tahir; Febrianto (Akademi Farmasi Yamasi Makassar, 2023)
Level of Knowledge of Antibiotic Use with Doctor's Prescription at Devan Pharmacy, Gowa Regency. A study was conducted on the Level of Knowledge of Antibiotic Use with Prescription at Devan Pharmacy, Gowa Regency in May - June 2022. The purpose of this study was to obtain information about the Level of Knowledge of Antibiotic Use with Prescription at Devan Pharmacy, Gowa Regency in 2022. This type of research is descriptive research using a questionnaire as a data collection instrument. The sample in this study were patients who wanted to buy antibiotics at the Devan pharmacy, Gowa Regency, totaling 30 people. The results showed that the level of knowledge of using antibiotics with a doctor's prescription at Devan Pharmacy was in the good enough category, namely (57%)